2011
DOI: 10.1007/s13213-011-0239-0
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of olive knot disease by Bacillus subtilis isolated from olive leaves

Abstract: We evaluated the biocontrol efficacy of a Bacillus subtilis strain isolated from symptomless olive leaves against the olive knot disease pathogen Pseudomonas savastanoi pv. savastanoi. Bacillus subtilis F 1 and F-4 displayed antibacterial activity against the pathogen. In planta, only B. subtilis F 1 significantly reduced the weight of knots caused by P. savastanoi pv. savastanoi IVIA 1628 and Aw 9 , whereas copper treatment was effective only when using strain Aw 9 , thus a reduction of 50% was obtained. Prel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Bacillus spp. isolated from olive leaves were tested against Pss, revealing promising results in both in vitro and in planta assays 50,51 . In the present study, other genera (Alcaligenes, Brevundimonas, Curtobacterium and Arthrobacter) were also strongly correlated with asymptomatic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus spp. isolated from olive leaves were tested against Pss, revealing promising results in both in vitro and in planta assays 50,51 . In the present study, other genera (Alcaligenes, Brevundimonas, Curtobacterium and Arthrobacter) were also strongly correlated with asymptomatic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The benzimidazole (MBC) fungicide was used in this experiment because of it efficacy in controlling Fusarium spp. [17,18]. A series of fungicide dilutions (in µg mL −1 active ingredient) were prepared from a 100 µg mL −1 stock solution.…”
Section: Fungicide Sensitivity Of Fusarium On Amended Pda Platesmentioning
confidence: 99%
“…The control of PSS is exclusively based on the limitation of the first infection, thus, there is no effective measures exist for a strict control of this pathogen. Nevertheless, in the recent years, promoting results were obtained by using microbial antagonists effective in vitro (Lavermicocca et al, 2002;Rokni Zadeh et al, 2008;Kacem et al, 2009;Krid et al, 2010). Krid et al, (2010Krid et al, ( , 2012 studied the effect of two B. subtilis strains toward PSS and found that they formed an inhibition zone ranging from 12 to 25 mm of diameter depend the method of co-inoculation.…”
Section: Figurementioning
confidence: 99%
“…Nevertheless, in the recent years, promoting results were obtained by using microbial antagonists effective in vitro (Lavermicocca et al, 2002;Rokni Zadeh et al, 2008;Kacem et al, 2009;Krid et al, 2010). Krid et al, (2010Krid et al, ( , 2012 studied the effect of two B. subtilis strains toward PSS and found that they formed an inhibition zone ranging from 12 to 25 mm of diameter depend the method of co-inoculation. El Hassni et al, (2007) showed that B. pumilus, R. aquatilis B. cereus had exhibited a high inhibition toward mycelial growth of Fusarium oxysporum f.sp albedinis (70-77%), and its sporulation.…”
Section: Figurementioning
confidence: 99%